Field scale biodegradation of total petroleum hydrocarbons and soil restoration by Ecopiles: microbiological analysis of the process - Martínez-Cuesta, Ruben; Conlon, Robert; Wang, Mutian; Blanco-Romero, Esther; Durán, David; Redondo-Nieto, Miguel; Dowling, David; Garrido-Sanz, Daniel; Martin, Marta; Germaine, Kieran; Rivilla, Rafael (Frontiers in Microbiology, 2023)
Ecopiling is a method for biodegradation of hydrocarbons in soils. It derives from Biopiles, but phytoremediation is added to biostimulation with nitrogen fertilization and bioaugmentation with local bacteria. We have constructed eight Ecopiles with soil heavily polluted with hydrocarbons in Carlow (Ireland). The aim of the study was to analyze changes in the microbial community during ecopiling. In the course of 18 months of remediation, total petroleum hydrocarbons values decreased in 99% and 88% on average for aliphatics and aromatics, respectively, indicating a successful biodegradation. Community analysis showed that bacterial alfa diversity, as Shannon Index, increased with the degradation of hydrocarbons, with starting average value of 7.59 and final average value of 9.38. To observe differences regarding the beta diversity between samples, a PCoA ordination was performed using Bray-Curtis distances, where the two first principal components (PCs) explain the 17% and 14% of the observed variance, respectively. The results show that samples tend to cluster by sampling time instead of by Ecopile. This clustering pattern is supported by the hierarchical clustering analysis, where most samples from the same timepoint clustered together. We also used DSeq2 to determine the differential abundance of bacterial populations in Ecopiles at the beginning and the end of the treatment. While TPHs degraders are more abundant at the start of the experiment, these populations are substituted by bacterial populations typical of clean soils by the end of the biodegradation process. Similar results are found for the fungal community, indicating that the microbial community follows a succession along the bioremediation process. This succession starts with a TPH degraders or tolerant enriched community, and finish with a microbial community typical of clean soils.